Rebecca Black’s Friday vs Raef’s It’s Jumu’ah: a comparative analysis of cultural representation - Othman, Khairiah; Abdul Malik, Faridah; Zulkipli, Muhammad Fakhrullah (2019)
Utilizing English songs in English classes has been an effective teaching tool for ESL teachers. Not only the students enjoy their English classes which eventually will improve their motivation to learn the language, but also more importantly, their proficiency for instance, in terms of pronunciation, grammatical structures and vocabulary will be enhanced. Nevertheless, the interconnectedness between English songs and western culture may create uneasiness on some non-native learners as some lyrics of the songs may not be in-line with their value system and may not be appropriate for them to sing. This article aims to highlight the presence of Western values in an English song which may not be congruent with Islamic principles and the presence of Islamic values when the lyrics is changed. The song of Rebecca Black’s Friday and Raef’s It’s Jumu’ah will be analysed. The findings indicate the presence of some un-Islamic elements in the English song and the presence of some Islamic values in Raef’s It’s Jumu’ah, in addition to seventeen Islamic English words. It is hoped that this study will make ESL teachers aware of the need to use appropriate English songs in ESL classes, particularly when teaching Muslim learners. Keywords: song, culture, Muslims, ESL/EFL, Islamic English